Low-expansion tampon and preparation method thereof
By combining cotton fiber pretreatment with bio-based adhesives, a tightly locked structure is formed, solving the problem of unstable expansion of traditional tampons and improving the user experience and safety of the product.
Patent Information
- Application Number
- CN202511330836.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-17
- Publication Date
- 2025-10-21
- Estimated Expiration
- 2045-09-17
AI Technical Summary
Traditional tampons tend to over-expand after absorbing liquid, causing discomfort and leakage. In addition, their physical compression structure is unstable under changes in temperature and humidity, affecting the user experience.
By pre-treating the cotton fibers and applying bio-based adhesives between the single layers of cotton fibers, a tightly locked overall structure is formed to reduce expansion and maintain structural integrity. Microwave heating and pressing processes are used to ensure dimensional stability.
The tampon maintains its structural integrity after absorbing liquid, reduces the risk of leakage, improves the user experience, and enhances the safety and antibacterial properties of the product.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sanitary products, and in particular to a low-expansion tampon and a preparation method thereof. Background Art
[0002] Tampons, as an internal feminine hygiene product, are gaining increasing popularity among consumers due to their convenience and comfort. Traditional tampons are primarily made of highly absorbent materials such as cotton fibers, and their core function is to absorb menstrual blood to prevent leakage. However, existing tampon products still have inherent flaws that affect user experience and product performance.
[0003] First, a significant problem with traditional tampons is their uncontrolled excessive expansion after absorbing liquid. Cotton fibers, the primary absorbent material, have natural physical properties that cause them to expand rapidly upon contact with liquid. While this expansion is essential for achieving absorption, excessive expansion or uneven expansion can lead to two major problems: first, it can cause discomfort during menstruation; second, before the tampon reaches saturation absorption, its drastic change in shape can disrupt its fit with the vaginal wall, creating gaps and potentially causing side leakage or seepage, which defeats the purpose of the product design.
[0004] Secondly, to control expansion and maintain the compressed shape of the tampon before insertion, traditional processes typically rely on high-pressure physical compression. However, this structure formed by simple physical compression can rebound during storage and transportation due to changes in ambient temperature and humidity, resulting in unstable product dimensions and affecting smooth insertion. More importantly, once exposed to liquid, this physical restraint is easily broken, making it unable to effectively prevent subsequent excessive expansion.
[0005] Although the industry has tried to direct liquid flow and manage swelling morphology by changing the weave pattern or external grooves of the sliver, these improvements do not fundamentally change the swelling characteristics of the absorbent core material. Summary of the Invention
[0006] The main purpose of the present invention is to propose a low-expansion tampon and a preparation method thereof; by pre-treating the cotton fibers to initially reduce their expansibility, and then by applying a bio-based adhesive between the single layers of cotton fibers, the cotton fibers can be effectively bonded to form a tightly locked overall structure, so that the manufactured tampon can maintain its structural integrity even after absorbing liquid, is not prone to leakage, and improves the product user experience.
[0007] To achieve the above object, the present invention provides a method for preparing a low-expansion tampon, comprising the following steps: S1. Combing the pretreated cotton fibers, stacking them into a single layer of cotton fibers after combing, coating the single layer of cotton fibers with a bio-based adhesive, and then covering it with another single layer of cotton fibers to obtain a double layer of cotton fibers. The double layers of cotton fibers are stacked to obtain a cotton mesh layer, which is then wrapped with a non-woven fabric and pressed into a strip-shaped fiber layer. S2. Fixing a cotton thread at the center of the strip fiber layer, with the tail end of the cotton thread exposed 10-20 cm outside the strip fiber layer, then curling the strip fiber layer to form a long cylindrical absorbent body, pressing and forming it in a former, and then performing microwave heating to obtain a tampon body; S3. Compress the tampon body into the catheter to obtain a low-expansion tampon.
[0008] Preferably, the preparation method of the pretreated cotton fiber in step S1 is as follows: the cotton fiber is immersed in a sodium sulfate aqueous solution, taken out and dried, and then treated with plasma to obtain the pretreated cotton fiber.
[0009] Further preferably, the concentration of the sodium sulfate aqueous solution is 20-30wt%. When treated with the sodium sulfate aqueous solution at this concentration, the cotton fibers can shrink and dehydrate through osmotic pressure, making the fiber structure tighter and losing some flexibility, which can preliminarily reduce the expansion of the cotton fibers. The surface is then etched by plasma to expose more active groups, which is beneficial to improving the interfacial bonding strength between the modified adhesive and the pretreated cotton fibers.
[0010] Preferably, the weight of the single layer of cotton fiber in step S1 is 12-16 g / m 2 .
[0011] Preferably, the method for preparing the bio-based adhesive in step S1 comprises the following steps: The gelatin is soaked in cold water for swelling, and then heated to dissolve, isoliquiritin and formaldehyde aqueous solution are added, ultrasonically dispersed under a nitrogen atmosphere, the pH is adjusted to 4-6, the temperature is increased to react, and after the reaction is completed, the solvent is evaporated under reduced pressure, and the residue is spray-dried to obtain a gelatin complex; L-tryptophan is added to deionized water, acetic acid aqueous solution is added dropwise, the pH value is adjusted to 5-6, and then the gelatin complex, polyvinyl alcohol, dialdehyde starch and hydroxyethyl cellulose are added thereto, the mixture is heated and stirred, and after the reaction is completed, the mixture is cooled to obtain a bio-based adhesive.
[0012] Further preferably, the mass ratio of the gelatin, isoliquiritin and formaldehyde aqueous solution is 2-5:1-3:6-10; and the concentration of the formaldehyde aqueous solution is 30-40wt%.
[0013] More preferably, the temperature of the temperature-raising reaction is 55-75° C., and the reaction time is 3-5 h.
[0014] Further preferably, the mass ratio of the L-tryptophan, gelatin complex, polyvinyl alcohol, dialdehyde starch, and hydroxyethyl cellulose is 8-10:20-30:10-20:5-10:1-2.
[0015] More preferably, the heating and stirring temperature is 60-75° C., and the heating and stirring time is 1.5-2.5 h.
[0016] The preparation of the bio-based adhesive of the present invention is based on gelatin, polyvinyl alcohol and starch. First, isoliquiritin is grafted into the gelatin molecule so that isoliquiritin is more evenly dispersed in and stably immobilized in the three-dimensional network structure of the adhesive, which is conducive to exerting its long-lasting antibacterial properties. By introducing hydrophobic L-tryptophan into the adhesive system, on the one hand, the water resistance and dimensional stability of the adhesive can be improved; on the other hand, it can also react with dialdehyde starch to form a Schiff base to form a three-dimensional network structure, which not only greatly enhances the cohesion and mechanical strength of the adhesive, but also provides a physical basis for strongly binding cotton fibers and inhibiting their expansion in a dry state.
[0017] When the bio-based adhesive is coated on the pretreated cotton fibers and subsequently pressed and heated, it can bond with the pretreated cotton fibers through covalent bonds, firmly anchoring the adhesive on the fibers to form a tightly locked overall structure, ultimately giving the tampon better anti-swelling ability and dimensional stability.
[0018] Preferably, the weight of the non-woven fabric in step S1 is 30-50 g / m 2 .
[0019] Preferably, the temperature of the microwave heating in step S2 is 50-65° C., and the time of the microwave heating is 2-8 s.
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention discloses a method for preparing a low-expansion tampon, wherein cotton fibers are modified and pretreated, and then combed into a web to obtain a single layer of cotton fibers, and then a bio-based adhesive is coated on the single layer of cotton fibers, and then multiple layers are stacked and pressed, curled, pressed, and microwave-heated to obtain a tampon body. Due to the pretreatment of the cotton fibers, the fiber structure becomes tighter and loses some flexibility, which can initially reduce the expansion of the cotton fibers. Then, the surface of the cotton fibers is etched by plasma to expose more active groups, thereby improving the interfacial bonding strength between the pretreated cotton fibers and the bio-based adhesive. The three-dimensional network formed by the adhesive strongly binds the fibers. Combined with the pressing and microwave shaping processes, the adhesive forms a stable three-dimensional network between the fibers, locking the entire tampon body in a preset compressed state, ensuring the high quality stability and smooth use of the tampon in a dry state. Once it comes into contact with menstrual blood, the menstrual blood will destroy the bonding force of the adhesive, releasing the bond between the cotton fibers, and the tampon body will fully expand, thereby ensuring its good absorption capacity. (2) The present invention provides a bio-based adhesive, which uses biocompatible gelatin, polyvinyl alcohol, and starch as raw materials, reducing the risk of irritation and allergies to users and improving the safety of the product. By grafting isoliquiritin into the gelatin molecule and stably immobilizing it using a three-dimensional network structure, its migration and loss during use are avoided, which is beneficial for long-term antibacterial properties. By introducing hydrophobic L-tryptophan and reacting it with dialdehyde starch to produce a Schiff base reaction, the cohesive force of the adhesive is enhanced, and the cotton fibers can be effectively bonded to form a tightly locked overall structure, so that the tampon can maintain its structural integrity even after absorbing liquid, and is not easily deformed or loosened, thereby improving the user experience of the product. DETAILED DESCRIPTION
[0021] To avoid redundancy, the items used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified. Example 1
[0022] A method for preparing a low-expansion tampon comprises the following steps: S1. Comb the pretreated cotton fibers and lay them into a 15g / m 2 A single layer of cotton fiber is coated with a bio-based adhesive on the single layer of cotton fiber, and then covered with a single layer of cotton fiber to obtain a double layer of cotton fiber. The double layers of cotton fiber are stacked to obtain a cotton mesh layer, and a weight of 40g / m 2 The cotton mesh layer is wrapped with non-woven fabric and then pressed into a strip fiber layer; S2. Fixing a cotton thread at the center of the strip fiber layer, with the tail end of the cotton thread exposed 15 cm outside the strip fiber layer, then curling the strip fiber layer to form a long cylindrical absorbent body, pressing and forming it in a former, and then microwave heating at 60° C. for 5 seconds to obtain a tampon body; S3. Compress the tampon body into the catheter to obtain a low-expansion tampon.
[0023] The preparation method of the pretreated cotton fiber in step S1 is as follows: immersing the cotton fiber in a 25wt% sodium sulfate aqueous solution for 2 hours, taking out, drying, and then treating the pretreated cotton fiber with plasma. The plasma treatment conditions are as follows: vacuuming the plasma instrument and then introducing oxygen, setting the power to 160W, and treating for 5 minutes.
[0024] The method for preparing the bio-based adhesive in step S1 comprises the following steps: 15 g of gelatin was soaked in cold water for swelling, then heated to 50°C to dissolve, 10 g of isoliquiritin and 37.5 g of 35 wt% formaldehyde aqueous solution were added, and the pH was adjusted to 5 after ultrasonic dispersion under a nitrogen atmosphere. The temperature was raised to 65°C for reaction for 4 h. After the reaction was completed, the solvent was evaporated under reduced pressure, and the residue was spray-dried to obtain a gelatin complex; 8.8 g of L-tryptophan was added to 200 mL of deionized water, 10 g of 38 wt% acetic acid aqueous solution was added dropwise, and the pH was adjusted to 6. Then 24.7 g of gelatin complex, 12.5 g of polyvinyl alcohol, 8.6 g of dialdehyde starch and 1.5 g of hydroxyethyl cellulose were added thereto, and the mixture was heated and stirred at 70°C for 2 h. After the reaction was completed, the mixture was cooled to obtain a bio-based adhesive. Example 2
[0025] A method for preparing a low-expansion tampon comprises the following steps: S1. Comb the pretreated cotton fibers and lay them into a 12g / m 2 A single layer of cotton fiber is coated with a bio-based adhesive on the single layer of cotton fiber, and then covered with a single layer of cotton fiber to obtain a double layer of cotton fiber. The double layers of cotton fiber are stacked to obtain a cotton mesh layer. The weight is 30g / m 2 The cotton mesh layer is wrapped with non-woven fabric and then pressed into a strip fiber layer; S2. Fixing a cotton thread at the center of the strip fiber layer, with the tail end of the cotton thread exposed 10 cm outside the strip fiber layer, then curling the strip fiber layer to form a long cylindrical absorbent body, pressing and forming it in a former, and then heating it in a microwave at 50° C. for 8 seconds to obtain a tampon body; S3. Compress the tampon body into the catheter to obtain a low-expansion tampon.
[0026] The preparation method of the pretreated cotton fiber in step S1 is as follows: immersing the cotton fiber in a 20wt% sodium sulfate aqueous solution for 3 hours, taking out, drying, and then treating the pretreated cotton fiber with plasma. The plasma treatment conditions are as follows: vacuuming the plasma instrument and then introducing oxygen, setting the power to 160W, and treating for 5 minutes.
[0027] The method for preparing the bio-based adhesive in step S1 comprises the following steps: 12 g of gelatin was soaked in cold water for swelling, then heated to 50°C to dissolve, 6 g of isoliquiritin and 36 g of 40 wt% formaldehyde aqueous solution were added, and the pH was adjusted to 6 after ultrasonic dispersion under a nitrogen atmosphere. The temperature was raised to 55°C for reaction for 4 h. After the reaction was completed, the solvent was evaporated under reduced pressure, and the residue was spray-dried to obtain a gelatin complex; 8 g of L-tryptophan was added to 200 mL of deionized water, 10 g of 38 wt% acetic acid aqueous solution was added dropwise, and the pH was adjusted to 5. Then 20 g of gelatin complex, 10 g of polyvinyl alcohol, 5 g of dialdehyde starch and 1 g of hydroxyethyl cellulose were added thereto, and the mixture was heated and stirred at 60°C for 2.5 h. After the reaction was completed, the mixture was cooled to obtain a bio-based adhesive. Example 3
[0028] A method for preparing a low-expansion tampon comprises the following steps: S1. Comb the pretreated cotton fibers and lay them into a 16g / m 2 A single layer of cotton fiber is coated with a bio-based adhesive on the single layer of cotton fiber, and then covered with a single layer of cotton fiber to obtain a double layer of cotton fiber. The double layers of cotton fiber are stacked to obtain a cotton mesh layer, and a weight of 50g / m 2 The cotton mesh layer is wrapped with non-woven fabric and then pressed into a strip fiber layer; S2. Fixing a cotton thread at the center of the strip fiber layer, with the tail end of the cotton thread exposed 20 cm outside the strip fiber layer, then curling the strip fiber layer to form a long cylindrical absorbent body, pressing and forming it in a former, and then heating it in a microwave at 65° C. for 2 seconds to obtain a tampon body; S3. Compress the tampon body into the catheter to obtain a low-expansion tampon.
[0029] The preparation method of the pretreated cotton fiber in step S1 is as follows: immersing the cotton fiber in a 30wt% sodium sulfate aqueous solution for 2.5 hours, taking out, drying, and then treating the pretreated cotton fiber with plasma. The plasma treatment conditions are as follows: vacuuming the plasma instrument and then introducing oxygen, setting the power to 160W, and treating for 5 minutes.
[0030] The method for preparing the bio-based adhesive in step S1 comprises the following steps: 25 g of gelatin was soaked in cold water for swelling, then heated to 50°C to dissolve, 15 g of isoliquiritin and 50 g of 30 wt% formaldehyde aqueous solution were added, and the pH was adjusted to 4 after ultrasonic dispersion under a nitrogen atmosphere. The temperature was raised to 75°C for reaction for 3 h. After the reaction was completed, the solvent was evaporated under reduced pressure, and the residue was spray-dried to obtain a gelatin complex; 10 g of L-tryptophan was added to 200 mL of deionized water, 12 g of 38 wt% acetic acid aqueous solution was added dropwise, and the pH was adjusted to 6. Then 30 g of gelatin complex, 20 g of polyvinyl alcohol, 10 g of dialdehyde starch and 2 g of hydroxyethyl cellulose were added thereto, and the mixture was heated and stirred at 70°C for 1.5 h. After the reaction was completed, the mixture was cooled to obtain a bio-based adhesive.
[0031] Comparative Example 1 A method for preparing a low-swelling tampon is similar to that of Example 1, except that the cotton fibers are not pretreated. The method specifically comprises the following steps: S1. Comb the cotton fibers and lay them into a 15g / m² 2 A single layer of cotton fiber is coated with a bio-based adhesive on the single layer of cotton fiber, and then covered with a single layer of cotton fiber to obtain a double layer of cotton fiber. The double layers of cotton fiber are stacked to obtain a cotton mesh layer, and a weight of 40g / m 2 The cotton mesh layer is wrapped with non-woven fabric and then pressed into a strip fiber layer; S2. Fixing a cotton thread at the center of the strip fiber layer, with the tail end of the cotton thread exposed 15 cm outside the strip fiber layer, then curling the strip fiber layer to form a long cylindrical absorbent body, pressing and forming it in a former, and then microwave heating at 60° C. for 5 seconds to obtain a tampon body; S3. Compress the tampon body into the catheter to obtain a low-expansion tampon.
[0032] The method for preparing the bio-based adhesive in step S1 comprises the following steps: 15 g of gelatin was soaked in cold water for swelling, then heated to 50°C to dissolve, 10 g of isoliquiritin and 37.5 g of 35 wt% formaldehyde aqueous solution were added, and the pH was adjusted to 5 after ultrasonic dispersion under a nitrogen atmosphere. The temperature was raised to 65°C for reaction for 4 h. After the reaction was completed, the solvent was evaporated under reduced pressure, and the residue was spray-dried to obtain a gelatin complex; 8.8 g of L-tryptophan was added to 200 mL of deionized water, 10 g of 38 wt% acetic acid aqueous solution was added dropwise, and the pH was adjusted to 6. Then 24.7 g of gelatin complex, 12.5 g of polyvinyl alcohol, 8.6 g of dialdehyde starch and 1.5 g of hydroxyethyl cellulose were added thereto, and the mixture was heated and stirred at 70°C for 2 h. After the reaction was completed, the mixture was cooled to obtain a bio-based adhesive.
[0033] Comparative Example 2 A method for preparing a low-swelling tampon is similar to that of Example 1, except that L-tryptophan is not added to the bio-based adhesive. The method specifically comprises the following steps: S1. Comb the pretreated cotton fibers and lay them into a 15g / m 2 A single layer of cotton fiber is coated with a bio-based adhesive on the single layer of cotton fiber, and then covered with a single layer of cotton fiber to obtain a double layer of cotton fiber. The double layers of cotton fiber are stacked to obtain a cotton mesh layer, and a weight of 40g / m 2 The cotton mesh layer is wrapped with non-woven fabric and then pressed into a strip fiber layer; S2. Fixing a cotton thread at the center of the strip fiber layer, with the tail end of the cotton thread exposed 15 cm outside the strip fiber layer, then curling the strip fiber layer to form a long cylindrical absorbent body, pressing and forming it in a former, and then microwave heating at 60° C. for 5 seconds to obtain a tampon body; S3. Compress the tampon body into the catheter to obtain a low-expansion tampon.
[0034] The preparation method of the pretreated cotton fiber in step S1 is as follows: immersing the cotton fiber in a 25wt% sodium sulfate aqueous solution for 2 hours, taking out, drying, and then treating the pretreated cotton fiber with plasma. The plasma treatment conditions are as follows: vacuuming the plasma instrument and then introducing oxygen, setting the power to 160W, and treating for 5 minutes.
[0035] The method for preparing the bio-based adhesive in step S1 comprises the following steps: 15 g of gelatin was soaked in cold water for swelling, then heated to 50°C to dissolve, 10 g of isoliquiritin and 37.5 g of 35 wt% formaldehyde aqueous solution were added, and the pH was adjusted to 5 after ultrasonic dispersion under a nitrogen atmosphere. The temperature was raised to 65°C for reaction for 4 h. After the reaction was completed, the solvent was evaporated under reduced pressure, and the residue was spray-dried to obtain a gelatin complex; 24.7 g of the gelatin complex, 12.5 g of polyvinyl alcohol, 8.6 g of dialdehyde starch and 1.5 g of hydroxyethyl cellulose were heated and stirred at 70°C for 2 h. After the reaction was completed, the mixture was cooled to obtain a bio-based adhesive.
[0036] Comparative Example 3 A method for preparing a low-swelling tampon is similar to that of Example 1, except that the gelatin complex is a mixture of gelatin and isoliquiritin, and specifically comprises the following steps: S1. Comb the pretreated cotton fibers and lay them into a 15g / m 2 A single layer of cotton fiber is coated with a bio-based adhesive on the single layer of cotton fiber, and then covered with a single layer of cotton fiber to obtain a double layer of cotton fiber. The double layers of cotton fiber are stacked to obtain a cotton mesh layer, and a weight of 40g / m 2The cotton mesh layer is wrapped with non-woven fabric and then pressed into a strip fiber layer; S2. Fixing a cotton thread at the center of the strip fiber layer, with the tail end of the cotton thread exposed 15 cm outside the strip fiber layer, then curling the strip fiber layer to form a long cylindrical absorbent body, pressing and forming it in a former, and then microwave heating at 60° C. for 5 seconds to obtain a tampon body; S3. Compress the tampon body into the catheter to obtain a low-expansion tampon.
[0037] The preparation method of the pretreated cotton fiber in step S1 is as follows: immersing the cotton fiber in a 25wt% sodium sulfate aqueous solution for 2 hours, taking out, drying, and then treating the pretreated cotton fiber with plasma. The plasma treatment conditions are as follows: vacuuming the plasma instrument and then introducing oxygen, setting the power to 160W, and treating for 5 minutes.
[0038] The method for preparing the bio-based adhesive in step S1 comprises the following steps: 15 g of gelatin was soaked in cold water for swelling, then heated to 50°C to dissolve, 10 g of isoliquiritin and 37.5 g of 35 wt% formaldehyde aqueous solution were added, and the pH was adjusted to 5 after ultrasonic dispersion under a nitrogen atmosphere. The temperature was raised to 65°C for reaction for 4 h. After the reaction was completed, the solvent was evaporated under reduced pressure, and the residue was spray-dried to obtain a gelatin complex; 8.8 g of L-tryptophan was added to 200 mL of deionized water, 10 g of 38 wt% acetic acid aqueous solution was added dropwise, and the pH was adjusted to 6. Then 24.7 g of gelatin complex, 12.5 g of polyvinyl alcohol, 8.6 g of dialdehyde starch and 1.5 g of hydroxyethyl cellulose were added thereto, and the mixture was heated and stirred at 70°C for 2 h. After the reaction was completed, the mixture was cooled to obtain a bio-based adhesive.
[0039] Performance Testing The tampons prepared in Examples 1-3 and Comparative Examples 1-3 were randomly selected, 20 per group, and the push-out force of any 10 tampons after production was tested to calculate the average push-out force. The average push-out force of the remaining 10 tampons was tested after being placed at room temperature for 6 months. The absorption capacity was also tested, and when the absorption capacity exceeded 10 g, the tail end of the cotton thread was observed to see if there was liquid dripping. The test results are shown in Table 1 below: Table 1 Tampon performance test results
[0040] It can be seen from the experimental results in Table 1 that the tampon obtained by the present invention has good storage stability and good absorption performance, and can effectively prevent menstrual blood leakage.
[0041] The bio-based adhesive obtained in Example 1 and Comparative Example 3 was evenly coated on a glass sheet, and after solidification, it was immersed in water for 2 hours. After drying, 1 ml of a 10 5 Escherichia coli bacterial solution with a CFU / ml was added dropwise to the surface of a sterilized glass slide sample coated with a bio-based adhesive and cultured at 37°C for 8 h. 20 μL of the cultured bacterial solution was transferred and evenly spread on a solid culture medium. After cultured at 37°C for 24 h, the number of colonies on the culture medium was counted. A blank experiment was also performed. The antibacterial rate was calculated using the following formula (I): Antibacterial rate = (AB) / A×100%, formula (I) Among them, A is the number of colonies in the blank experiment, B is the number of colonies in the sample group experiment, The test results are shown in Table 2: Table 2 Antibacterial performance test results of bio-based adhesives Antibacterial rate (%) Example 1 99.9 Comparative Example 3 90.3 From the results in Table 2, it can be seen that the bio-based adhesive prepared by the present invention has a good antibacterial effect.
[0042] The above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Those skilled in the art will readily appreciate that the present invention is susceptible to various modifications and variations. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention shall be included within the scope of the present invention.
Claims
1. A method for preparing a low-expansion tampon, characterized in that: The steps include: S1. Combing the pretreated cotton fibers, stacking them into a single layer of cotton fibers after combing, coating the single layer of cotton fibers with a bio-based adhesive, and then covering it with another single layer of cotton fibers to obtain a double layer of cotton fibers. The double layers of cotton fibers are stacked to obtain a cotton mesh layer, which is then wrapped with a non-woven fabric and pressed into a strip-shaped fiber layer. S2. Fixing a cotton thread at the center of the strip fiber layer, with the tail end of the cotton thread exposed 10-20 cm outside the strip fiber layer, then curling the strip fiber layer to form a long cylindrical absorbent body, pressing and forming it in a former, and then performing microwave heating to obtain a tampon body; S3. Compress the tampon body into the catheter to obtain a low-expansion tampon.
2. The preparation method according to claim 1, wherein: The preparation method of the pretreated cotton fiber in step S1 is as follows: the cotton fiber is immersed in a sodium sulfate aqueous solution, taken out and dried, and then treated with plasma to obtain the pretreated cotton fiber.
3. The preparation method according to claim 2, wherein: The concentration of the sodium sulfate aqueous solution is 20-30 wt %.
4. The preparation method according to claim 1, wherein: The weight of the single layer of cotton fiber in step S1 is 12-16 g / m 2 .
5. The preparation method according to claim 1, characterized in that The method for preparing the bio-based adhesive in step S1 comprises the following steps: The gelatin is soaked in cold water for swelling, and then heated to dissolve, isoliquiritin and formaldehyde aqueous solution are added, ultrasonically dispersed under a nitrogen atmosphere, the pH is adjusted to 4-6, the temperature is increased to react, and after the reaction is completed, the solvent is evaporated under reduced pressure, and the residue is spray-dried to obtain a gelatin complex; L-tryptophan is added to deionized water, acetic acid aqueous solution is added dropwise, the pH value is adjusted to 5-6, and then the gelatin complex, polyvinyl alcohol, dialdehyde starch and hydroxyethyl cellulose are added thereto, the mixture is heated and stirred, and after the reaction is completed, the mixture is cooled to obtain a bio-based adhesive.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the gelatin, isoliquiritin and formaldehyde aqueous solution is 2-5:1-3:6-10.
7. The preparation method according to claim 5, characterized in that: The heating and stirring temperature is 60-75° C., and the heating and stirring time is 1.5-2.5 h.
8. The preparation method according to claim 1, wherein: The weight of the non-woven fabric in step S1 is 30-50 g / m 2 .
9. The preparation method according to claim 1, wherein: The temperature of microwave heating in step S2 is 50-65° C., and the time of microwave heating is 2-8 s.
10. A low expansion tampon, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Modified composite sponge dressing and preparation method thereof
CN104524620A
Anti-wrinkle modified cotton fiber and preparation method thereof
CN111235883A
Antibacterial and antifouling organic cotton and kapok blended yarns and preparation method thereof
CN112481760A
Tampon easy to push out and preparation method thereof
CN117297879A
Absorber of novel environment-friendly composite fiber sanitary towel as well as preparation method and application
CN120360781A